The Association of Surgical Margins and Local Recurrence in Women with Ductal Carcinoma In Situ Treated with Breast-Conserving Therapy: A Meta-Analysis - Marinovich, M. Luke (Ann Surg Oncol, 2016)
PURPOSE: There is no consensus on adequate negative margins in breast-conserving surgery (BCS) for ductal carcinoma in-situ (DCIS). We systematically review the evidence on margins in BCS for DCIS. METHODS: Study-level meta-analysis of local recurrence (LR), microscopic margin status and threshold distance for negative margins. LR proportion was modelled using random-effects logistic meta-regression (frequentist), and network meta-analysis (Bayesian) that allows for multiple margin distances per study, adjusting for follow-up time. RESULTS: Based on 20 studies (LR: 865 of 7,883), odds of LR were associated with margin status (logistic: odds ratio (OR) 0.53 for negative vs positive/close [P<0.001]; network: OR=0.45 for negative vs positive). In logistic meta-regression, relative to >0 or 1mm, ORs for 2mm (0.51), 3 or 5mm (0.42) and 10mm (0.60) showed comparable significant reductions in the odds of LR. In the network analysis, ORs relative to positive margins for 2mm (0.32), 3mm (0.30) and 10mm (0.32) showed similar reductions in the odds of LR that were greater than for >0 or 1mm (0.45). There was weak evidence of lower odds at 2mm compared to >0 or 1mm (Relative OR=0.72, 95% credible interval [CrI] 0.47-1.08), and no evidence of a difference between 2mm and 10mm (Relative OR=0.99, 95% CrI 0.61-1.64). Adjustment for covariates, and analyses based only on studies using whole-breast radiotherapy, did not change findings. CONCLUSION: Negative margins in BCS for DCIS reduce the odds of LR; however, minimum margins distances above 2mm are not significantly associated with further reduced odds of LR in women receiving radiation.